Postmodernism in history : fear or freedom? - Southgate, Beverley (Routledge, 2003)
This original and thought-provoking study looks at the context of postmodernist thought in general cultural terms as well as in relation to history. Postmodernism in History traces philosophical precursors of postmodernism and identifies the roots of current concerns. Beverley Southgate describes the core constituents of postmodernism and provides a lucid and profound analysis of the current state of the debate. His main concern is to counter 'pomophobia' and to assert a positive future for historical study in a postmodern world.